2019
DOI: 10.1097/shk.0000000000001257
|View full text |Cite|
|
Sign up to set email alerts
|

CIRP Induces Neutrophil Reverse Transendothelial Migration in Sepsis

Abstract: Extracellular cold-inducible RNA-binding protein (CIRP) exaggerates inflammation in sepsis. Neutrophil reverse transendothelial migration (rTEM) allows neutrophils to migrate from tissues into the circulation. The phenotype of neutrophils following reverse migration is CD54CXCR1. We hypothesize that CIRP induces neutrophil rTEM in sepsis. Sepsis was induced in male C57BL/6 mice by cecal ligation and puncture (CLP), and at 5, 10, or 20 h after CLP, the frequencies of reversely migrated (RM) neutrophils were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 34 publications
2
42
0
1
Order By: Relevance
“…In the murine cremaster muscle ischemia and reperfusion injury model, lipid chemoattractant leukotriene B4 (LTB4) up‐regulated in the inflamed tissues induced neutrophil production of the proteolytic enzyme neutrophil elastase (NE), which disrupted JAM‐C at EC junction, thus facilitating neutrophil rTEM . This observation is in line with a recent study that showed increased NE and decreased JAM‐C in the lungs of mice with sepsis or injected with recombinant CIRP . In vitro neutrophil stimulation with recombinant CIRP significantly induced NE in cell culture supernatants, and the supernatant of eCIRP‐stimulated neutrophils dramatically decreased EC surface expression of JAM‐C, but not when NE blocking antibodies were added to the conditioned media .…”
Section: Reverse‐migrated Neutrophilssupporting
confidence: 77%
See 4 more Smart Citations
“…In the murine cremaster muscle ischemia and reperfusion injury model, lipid chemoattractant leukotriene B4 (LTB4) up‐regulated in the inflamed tissues induced neutrophil production of the proteolytic enzyme neutrophil elastase (NE), which disrupted JAM‐C at EC junction, thus facilitating neutrophil rTEM . This observation is in line with a recent study that showed increased NE and decreased JAM‐C in the lungs of mice with sepsis or injected with recombinant CIRP . In vitro neutrophil stimulation with recombinant CIRP significantly induced NE in cell culture supernatants, and the supernatant of eCIRP‐stimulated neutrophils dramatically decreased EC surface expression of JAM‐C, but not when NE blocking antibodies were added to the conditioned media .…”
Section: Reverse‐migrated Neutrophilssupporting
confidence: 77%
“…A recent study revealed that eCIRP also induces neutrophil rTEM. Septic WT mice had significantly more RM neutrophils in the circulation than septic CIRP −/− mice . Additionally, circulating RM neutrophils increased after intratracheal administration of recombinant CIRP to healthy mice, demonstrating that eCIRP is sufficient to induce neutrophil rTEM …”
Section: Reverse‐migrated Neutrophilsmentioning
confidence: 92%
See 3 more Smart Citations